Software engineering ontologies and their implementation - Wongthongtham, Pornpit; Chang, Elizabeth; Dillon, Tharam S.; Sommerville, I. (ACTA Publishing, 2005)
In this paper, we propose a new approach to software engineering. We organize software engineering concepts, ideas and knowledge along with software development methodologies, tools and techniques into ontologies and use them as a basis for classifying the concepts in communication and allowing knowledge sharing. The explanation of software engineering knowledge formed in our ontologies clarifies the software engineering concepts, thereby making them not only explicit but also aiding in the formalization of a consistent use by team developers. Furthermore, the ontology form can be understood by computers.